A Review of the Application of Heterostructure Catalysts in Hydrogen Evolution Reaction. Issue 14 (11th April 2022) - Dong, Shizhi; Li, Yanshuai; Zhao, Zhilong; Li, Ruichuan; He, Jiaqi; Yin, Jinpeng; Yan, Bing; Zhang, Xing
Abstract: Hydrogen energy as a significant part of clean energy in the future has been widely studied. Hydrogen production from electric cracking water is the most effective and mature development method at present. Heterostructured electrocatalysts are favored due to their low overpotential, excellent assembly structure and good electron transfer ability. Consequently this paper reviews the development of heterogeneous electrocatalysts, the measurement parameters of electrocatalytic hydrogen evolution reaction (HER), and related research progress, and gives the hydrogen evolution mechanism in acidic, alkaline and neutral environments. Finally, we explain the essential development direction and severe challenges in this field. Abstract : This paper reviews the progress of research on heterostructured catalysts for electrocatalytic hydrogen precipitation reactions. The excellent charge transport capability of heterostructures and the multilevel constitutive properties are extremely widely studied. In this paper, heterostructured catalysts from transition metals as well as alloys and compounds are described in detail. Non‐metallic‐based heterostructured electrocatalysts are also briefly mentioned. Prospects for related systems are also presented.